Caffeine as an indicator of human fecal contamination in the Sinos River: a preliminary study - R Linden (Brazilian Journal of Biology)
The preservation of hydric resources is directly related to fecal contamination monitoring, in order to allow the development of strategies for the management of polluting sources. In the present study, twenty-five water samples from six water public supply collection sites were used for the evaluation of the presence of caffeine, total and fecal coliforms. Caffeine was detected in all samples, with concentrations ranging from 0.15 ng mL–1 to 16.72 ng mL–1. Total coliforms were detected in all samples, with concentrations in the range of 52 NMP/100 mL to higher than 24196 NMP/100 mL, whether the concentration range for fecal coliforms was in the range of below 1 NMP/100 mL to 7800 NMP/100 mL. No significant correlation was found between total coliforms and caffeine concentrations (rs = 0.35, p = 0.09). However, a moderate correlation between fecal coliforms and caffeine concentrations was found (rs = 0.412, p <0.05), probably indicating a human source for these bacteria. Caffeine determination in water may be a useful strategy to evaluate water contamination by human fecal waste.